2017
DOI: 10.1248/bpb.b17-00111
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Prescription Pattern of Drugs for Hematological Malignancies in Japan from 2010–2014

Abstract: The number of elderly patients with hematologic malignancies has been steadily increasing with the aging of society. However, little research has been conducted to evaluate the prescription status of drugs for such diseases in Japan. Therefore, the aims of this study were to identify the patient population currently being prescribed drugs for hematologic malignancies in Japan and the direction of drug development. To examine the prescription pattern of drugs for the treatment of hematological malignancies in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Our results demonstrated that the mainstream of the current drug development focusing on anticancer drugs and especially on molecular targeted drugs, 25,26 and the highest ratio of molecular targeted agents in prescription pattern of drugs was observed in treatment of hematologic malignancies in Japan. 27,28 The findings of the present study suggested that medical costs for cancer as well as other diseases have continuously increased, although the pace of the increase may decline if precision medicine or related regulations are properly introduced. Ishii et al reported that there was little interest in cost analyses in cancer treatments in Japan, as most of the cost is managed by the government through the National Health Insurance system.…”
Section: Discussionmentioning
confidence: 70%
“…Our results demonstrated that the mainstream of the current drug development focusing on anticancer drugs and especially on molecular targeted drugs, 25,26 and the highest ratio of molecular targeted agents in prescription pattern of drugs was observed in treatment of hematologic malignancies in Japan. 27,28 The findings of the present study suggested that medical costs for cancer as well as other diseases have continuously increased, although the pace of the increase may decline if precision medicine or related regulations are properly introduced. Ishii et al reported that there was little interest in cost analyses in cancer treatments in Japan, as most of the cost is managed by the government through the National Health Insurance system.…”
Section: Discussionmentioning
confidence: 70%
“…19 This is expected to encourage increased R&D by Japanese pharmaceutical companies, especially in therapeutic areas where contributions have been made mainly by global pharmaceutical companies, resulting in the Japanese pharmaceutical market becoming more comparable to the global market. Actually, several reports have showed an upward R&D trend, especially in oncologic drugs in Japan, [25][26][27][28][29][30] which is being accelerated through these schemes.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the Japanese market is unique. R&D for both ''L'' and N'' drugs has been encouraged under current regulations, [27][28][29] maybe in part because the new reward premium system has been working well, Figure 7. Concept of repricing for market expansion.…”
Section: Future Perspectives Of the Japanese Drug Pricing Systemmentioning
confidence: 99%
“…As discussed above, the Japanese market is unique. R&D for both “L” and N” drugs has been encouraged under current regulations, 27–29 maybe in part because the new reward premium system has been working well, encouraging the R&D of drugs that meet medical needs in Japan such as anti-cancer drugs and drugs for intractable diseases, although we acknowledge that there are several inconsistencies with regard to repricing for market expansion. This reward system has been continued, which is encouraging leading pharmaceutical companies to enter the niche market where medical needs are quite high due to the small number of patients.…”
Section: Future Perspectives Of the Japanese Drug Pricing Systemmentioning
confidence: 99%